2003
DOI: 10.1159/000070098
|View full text |Cite
|
Sign up to set email alerts
|

Glass Needle-Mediated Microinjection of Macromolecules and Transgenes into Primary Human Mesenchymal Stem Cells

Abstract: Human mesenchymal stem cells (hMSCs) are multipotent cells that can differentiate into various tissue types, including bone, cartilage, tendon, adipocytes, and marrow stroma, making them potentially useful for human cell and gene therapies. Our objective was to demonstrate the utility of glass needle-mediated microinjection as a method to deliver macromolecules (e.g. dextrans, DNA) to hMSCs for cell and molecular biological studies. hMSCs were isolated and cultured using a specific fetal bovine serum, prescree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Strong GFP expression in the transfected human MSCs was observed 24 hours and 48 hours post transfection (Figure 1, [60]). Similarly, Tsulaia et al performed the nuclear microinjection using a glass needle of 275 nm in diameter and achieved high transgene expression in human MSCs [161].…”
Section: Microinjectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong GFP expression in the transfected human MSCs was observed 24 hours and 48 hours post transfection (Figure 1, [60]). Similarly, Tsulaia et al performed the nuclear microinjection using a glass needle of 275 nm in diameter and achieved high transgene expression in human MSCs [161].…”
Section: Microinjectionmentioning
confidence: 99%
“…Transfection with the plasmid containing collagen type II␣1 exhibited only a negligible efficiency, mainly because collagen type II is not expressed in the MSCs [58]. Tsulaia et al discovered that the structure of plasmid DNA plays an important role to regulate transgene expression and that a supercoiled DNA induced higher transfection efficiency (∼5-fold) than its linearized form after delivery into human MSCs via microinjection [161]. In addition, the influence of the types of the delivered nucleic acid material has been demonstrated that nucleofection of MSCs with mRNA resulted in a significantly higher protein expression than DNA transfection [178].…”
Section: Nucleic Acid Materialsmentioning
confidence: 99%
“…Pulled glass micropipettes with tip diameters ranging from hundreds of nanometers to a few micrometers are frequently fabricated for cell studies (Stephens and Pepperkok 2001;Tsulaia et al 2003;King 2004;Matsuoka and Saito 2006). Although glass micropipettes are currently the biologist's tool of choice, they suffer from a few drawbacks, such as fragility, a relatively large size compared to the cells' dimensions, and an inability to carry out electrical measurements concurrently with injection (Stephens and Pepperkok 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, microinjection using microcapillaries has been widely †This paper was presented at the 9 th Asian International Conference on Fluid Machinery (AICFM9), Jeju, Korea, October [16][17][18][19]2007.recommended for publication in revised form by Associate Editor Keum-Sik Hong exploited to inject proteins, peptides, and genetic materials [5,6]. However, damage problems arising from using microcapillaries still remain due to the shape and inaccurate displacement of the device.…”
Section: Introductionmentioning
confidence: 99%